Clinical Unmet Needs and Treatment Patterns of Paediatric Psoriasis Patients: A Real-World Evidence Study in Spain - R. de Lucas; A. Vicente; C. Richardson; J. Lucas; L. Gillespie-Akar; L. Gómez Labrador; A. Torrelo (Elsevier, 2023)
Background and objective: Real-world evidence of paediatric psoriasis (PsO) is lacking in Spain. The purpose of this study was to identify physician-reported disease burden and current treatment patterns in a real-world paediatric PsO patient cohort in Spain. This will enhance our understanding of the disease and contribute to the development of regional guidelines. Material and method: This retrospective analysis of a cross-sectional market research survey assessed the clinical unmet needs and treatment patterns in patients with paediatric PsO in Spain, as reported by their primary care and specialist physicians, using data collected as part of the Adelphi Real World Paediatric PsO Disease-Specific Program (DSP™) between February and October 2020. Results: Survey data from 57 treating physicians were included (71.9% [N = 41] dermatologists, 17.6% [N = 10] general practitioners/primary care physicians, and 10.5% [N = 6] paediatricians); the final analysis included 378 patients. At sampling, 84.1% (318/378) of patients had mild disease, 15.3% (58/378) had moderate disease and 0.5% (2/378) had severe disease. Retrospectively reported physician-judged severity at the time of PsO diagnosis recorded 41.8% (158/378) of patients with mild disease, 51.3% (194/378) with moderate disease and 6.9% (26/378) with severe disease. Overall, 89.3% (335/375) of patients were currently receiving topical PsO therapy, while 8.8% (33/375), 10.4% (39/375) and 14.9% (56/375) of patients were currently receiving phototherapy, conventional systemics and biologics, respectively. Conclusions: These real-world data reflect the current burden and treatment landscape of paediatric PsO in Spain. The management of patients with paediatric PsO could be improved by further educating healthcare professionals and developing regional guidelines. Resumen: Antecedente y objetivo: En España se carece de evidencia sobre psoriasis (PsO) pediátrica en el mundo real. El objetivo de este estudio fue identificar la carga de la enfermedad reportada por el facultativo y los patrones actuales de tratamiento en una cohorte de pacientes psoriásicos pediátricos en el mundo real. Ello ampliará nuestra comprensión de la enfermedad y contribuirá al desarrollo de directrices regionales. Material y método: Este análisis retrospectivo transversal de una encuesta de investigación mercado evaluó las necesidades clínicas no satisfechas y los patrones de tratamiento en pacientes con PsO pediátrica en España, según lo reportado por sus médicos de atención primaria y especialistas, utilizando datos recopilados como parte del Disease-specific program (DSP™) de Adelphi para PsO pediátrica en el mundo real, entre los meses de febrero y octubre de 2020. Resultados: Se incluyeron los datos de la encuesta realizada a 57 facultativos médicos tratantes (71,9% [N = 41] de dermatólogos, 17,6% [N = 10] de médicos generales de atención primaria y 10,5% [N = 6] de pediatras); el análisis final incluyó 378 pacientes. En la muestra, el 84,1% (318/378) de los pacientes padeció enfermedad leve, el 15,3% (58/378) enfermedad moderada y el 0,5% (2/378) enfermedad severa. De acuerdo con el reporte retrospectivo, la gravedad juzgada por el facultativo en el momento de diagnosticarse la PsO pediátrica registró un 41,8% (158/378) de pacientes con enfermedad leve, un 51,3% (194/378) con enfermedad moderada y un 6,9% (26/378) con enfermedad severa. En general, el 89,3% (335/375) de los pacientes recibía en la actualidad terapia tópica para PsO pediátrica, mientras que el 8,8% (33/375), el 10,4% (39/375) y el 14,9% (56/375) de los pacientes recibía en la actualidad fototerapia, sistémicos y biológicos convencionales, respectivamente. Conclusiones: Estos datos del mundo real reflejan la carga actual y el panorama de la PsO pediátrica en España. El manejo de los pacientes pediátricos podría mejorar, formando aún más a los profesionales sanitarios y desarrollando directrices regionales.